STRATEGI PEMBELAJARAN EVERY ONE IS A TEACHER HERE SEBAGAI UPAYA PENINGKATAN PRESTASI BELAJAR SISWA PADA MATA PELAJARAN FIQIH DI MI MUHAMMADIYAH PROGRAM KHUSUS KENTENG NOGOSARI BOYOLALI - Ngatimin Ngat; Mujiburrohman Mujib; Meti Fatimah Meti (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2023)
The purpose of this study was to determine the learning strategy of every one is techer here as an effort to increase student motivation and achievement in fiqh subjects at MI Muhammadiyah Kenteng Nogosari Special Program. This type of research is classroom action research which focuses on efforts to change the existing real conditions towards the expected conditions. This study uses a series of four activities carried out in repeated cycles. There are four main activities in each cycle, namely planning, action, observation, and reflection. The results showed that through the learning model approach, every one is a teacher here can increase motivation and achievement in learning the material fiqh to reach heaven through sunnah prayers for MIM students of the Kenteng Nogosari Special Program. This is evidenced by the students' complete learning, the completeness score (KKM ≥ 75) in the initial test was 8 people or 26.66%, and in the first cycle test it increased to 19 people or 63.33% and in cycle II it increased again to 28 people or 93.33%.